2013
DOI: 10.5812/jjm.5092
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasitic Infections in Chronic Psychiatric Patients in Sina Hospital Shahre-Kord, Iran

Abstract: Background: Although the number of infectious diseases has sharply decreased in last few decades, parasitic diseases persist in developing countries. On the other hand, chronic psychiatric patients tend to have low self-control, poor personal hygiene, long term institutionalization and extremely low self-care should be monitored for parasitic diseases since psychosocial conditions can contribute to an affinity for infectious diseases..Objectives: The aim of study was to investigate intestinal parasites in chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…In the present study, nine different parasites were identified six protozoa (B. hominis, C. parvum, Entameba histolytica/dispar, Cyclospora cayetanensis, Giardia intestinalis, & E. coli) and three worms (Ascaris lumbricoides, Hymenolepis nana, Entrobius vermicularis). but, the helminthes prevalence among psychiatric patients (2.3%) was much lower than previous reports from Iran (Mohammadi-Meskin et al, 2019), Nigeria (Eze et al, 2019;Otu-Bassey et al, 2019) and Tanzania (Nyundo et al, 2017), it was in accordance with the fact that in general, among chronic psychiatric patients in Sina Hospital Shahre-Kord, Iran (Khalili et al, 2013). Moreover, Sargent (1983) in USA reported T. trichiura, Ascaris lumbricoides, Giardia lamblia, and Entamoeba histolytica and added that annual examination and treatment could control parasitosis; but, complete eradication might require examination following home visits by the resident population.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the present study, nine different parasites were identified six protozoa (B. hominis, C. parvum, Entameba histolytica/dispar, Cyclospora cayetanensis, Giardia intestinalis, & E. coli) and three worms (Ascaris lumbricoides, Hymenolepis nana, Entrobius vermicularis). but, the helminthes prevalence among psychiatric patients (2.3%) was much lower than previous reports from Iran (Mohammadi-Meskin et al, 2019), Nigeria (Eze et al, 2019;Otu-Bassey et al, 2019) and Tanzania (Nyundo et al, 2017), it was in accordance with the fact that in general, among chronic psychiatric patients in Sina Hospital Shahre-Kord, Iran (Khalili et al, 2013). Moreover, Sargent (1983) in USA reported T. trichiura, Ascaris lumbricoides, Giardia lamblia, and Entamoeba histolytica and added that annual examination and treatment could control parasitosis; but, complete eradication might require examination following home visits by the resident population.…”
Section: Discussionsupporting
confidence: 76%
“…Psychiatric disorders are a group of disorders characterized by combination of abnormal thoughts, emotions, behaviors, and relationships with others (Khalili et al, 2013). Globally, psychiatric disorders rank the 3 rd most common disease, just after cancer and cardiovascular diseases (WHO, 2017), it was estimated that more than 25% of individuals; especially in developing countries develop one or more mental or behavioral disorders in their lifetime (Daré et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This was higher than 8.5% reported among the mentally retarded in Egypt [15], 29.5% reported among Institutionalized Mentally Disabled Individuals in Rasht, Northern Iran [7], 13.5% among patients of a Ghanaian psychiatry hospital [5] and 20.4% reported among mentally disabled children and adults of Urmia, Iran [16]. But lower than 43.5% was reported among mentally disabled individuals in Alexandria, Egypt [8], 68% was reported in chronic psychiatric patients in Sina Hospital Shahre-Kord, Iran [17]. Reasons for variation may be Location, sanitation, hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, many human settlements are characterized by poor hygiene habits, extensive interpersonal contact and increased dependency on care, which provide favorable conditions for the circulation and transmission of parasites and increased susceptibility to parasitic infections. This was revealed by reports of enteric parasitic infections in mental institutions, which indicate that rates of intestinal parasitic infections are higher among institutionalized persons than in the general population, even in developed countries [ 94 ]. It should be noted that we analyzed unpreserved stool samples from non-selected adults and identified Blastocystis in 46% of family members, compared to a lower figure of 32.5% among institutionalized patients.…”
Section: Discussionmentioning
confidence: 99%